2013
DOI: 10.1093/europace/eut159
|View full text |Cite
|
Sign up to set email alerts
|

The role of successful catheter ablation in patients with paroxysmal atrial fibrillation and prolonged sinus pauses: outcome during a 5-year follow-up

Abstract: Catheter ablation can eliminate both AF and prolonged sinus pauses in the majority of TBS patients. Nevertheless, such patients should be continuously followed-up, because gradual progression of sinus node dysfunction can occur after a long period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 16 publications
5
52
3
Order By: Relevance
“…31,32 Our ablation approach targeting non-PV triggers along with PVAI appeared to yield higher long-term success rate, which is in agreement with findings from earlier studies. [8][9][10]15,16 Study result of Sorgente et al 7 was more disappointing with a 6-year multiprocedure success rate of 50% in PAF patients which could be because of stricter definition of recurrence as well as their ostial ablation approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31,32 Our ablation approach targeting non-PV triggers along with PVAI appeared to yield higher long-term success rate, which is in agreement with findings from earlier studies. [8][9][10]15,16 Study result of Sorgente et al 7 was more disappointing with a 6-year multiprocedure success rate of 50% in PAF patients which could be because of stricter definition of recurrence as well as their ostial ablation approach.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several published reports have provided information on the outcomes of AF ablation. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] A meta-analysis evaluating studies reporting >3 years of outcome after catheter ablation (CA) found that nearly 80% multiprocedure success rates can be achieved in patients with PAF. 21 Few series have reported long-term outcomes of AF ablation over 5 years.…”
Section: See Editorial By Kumar and Michaudmentioning
confidence: 99%
See 1 more Smart Citation
“…76,84,85 In nonrandomized studies, a strategy of primary ablation for paroxysmal AF was superior to pacing and antiarrhythmic drug use. 84,86 Moreover, the majority of patients who underwent AF ablation no longer had an indication for pacing. However, continued surveillance is necessary in the postablation phase; early recurrences of atrial arrhythmias following an ablation may reproduce symptomatic sinus pauses.…”
Section: Pacing For the Treatment Of Sndmentioning
confidence: 99%
“…6, 7 Previous studies of AF ablation in patients with SSS have demonstrated the feasibility of CA and that both paroxysmal AF (PAF) and prolonged sinus pauses could be successfully eliminated in the majority of patients with bradycardia-tachycardia syndrome (BTS) over mid-to long-term follow up. [8][9][10][11] Previous studies, however, included a relatively small number of patients, with several confounders such as high age and previous PMI, and also did not consider structural remodeling in patients with SSS. Therefore, the clinical efficacy of CA for PAF in SSS patients and the mechanism and predictors of AF recurrence in this population remain unknown.…”
mentioning
confidence: 99%